Using the Discretionary Loan Loss Provisions Earnings Management by "Case Study of the International Bank for Trade and Finance" (Journal of Hama University, 2021)
This research aims to determine whether the loan losses provision is used for earnings managing in the International Bank for Trade and Finance, and to achieve the objective of the research, a loan loss provision model was applied, based on three variables that represent the non-discretionary provision; They are the non-performing loan balance at the beginning of the period, the change in non-performing loans, and the change in total loans. As for the discretionary component, it is the residual of the model and was calculated as the difference between the total provision and the non-discretionary one. To test whether International Bank for Trade and Finance practiced earnings management using the Loan Loss Provision; the impact of earnings before tax and provisions (EBTP) in the discretionary loan loss provisions (DDL) was studied. Quarterly data for the International Bank for Trade and Finance, for the period from 2013 to 2019, was relied on, and the data was analyzed using EViews 9. The results showed that the balance of non-performing loans at the beginning of the period has a positive role in creating the provision for loan losses, and there is also a positive impact of the earnings before tax and provisions in the discretionary loan loss provisions, meaning that the International Bank for Trade and Finance partially uses the discretionary loan losses provision motivated by earnings management and specifically to smooth income.